2008
DOI: 10.1371/journal.pntd.0000326
|View full text |Cite
|
Sign up to set email alerts
|

Stage- and Gender-Specific Proteomic Analysis of Brugia malayi Excretory-Secretory Products

Abstract: IntroductionWhile we lack a complete understanding of the molecular mechanisms by which parasites establish and achieve protection from host immune responses, it is accepted that many of these processes are mediated by products, primarily proteins, released from the parasite. Parasitic nematodes occur in different life stages and anatomical compartments within the host. Little is known about the composition and variability of products released at different developmental stages and their contribution to parasit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
147
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(171 citation statements)
references
References 75 publications
13
147
3
Order By: Relevance
“…The spectra were searched against the genomic databases for Bm and its endosymbiont Wolbachia (wBm). A total of 72,318 unique peptides were matched to 6,981 proteins (3,653,3,688,3,135,2,672, and 4,843 proteins) from AM, AF, MF, L3 larvae, and UTMF, respectively (SI Appendix, Table S1). Combining these data with those from a study performed previously on the Bm secretome (1) (that included 122 proteins not found in the current analyses) and 164 additional proteins (based on peptide matches that identified more than one protein; SI Appendix, Table S2) resulted in the definitive identification of a total of 7,103 proteins of the 11,610 proteins (∼61%) predicted from the genome (4) [ Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The spectra were searched against the genomic databases for Bm and its endosymbiont Wolbachia (wBm). A total of 72,318 unique peptides were matched to 6,981 proteins (3,653,3,688,3,135,2,672, and 4,843 proteins) from AM, AF, MF, L3 larvae, and UTMF, respectively (SI Appendix, Table S1). Combining these data with those from a study performed previously on the Bm secretome (1) (that included 122 proteins not found in the current analyses) and 164 additional proteins (based on peptide matches that identified more than one protein; SI Appendix, Table S2) resulted in the definitive identification of a total of 7,103 proteins of the 11,610 proteins (∼61%) predicted from the genome (4) [ Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Overcoming this limitation using highly sensitive approaches has lead to the identification of most of these proteins in B. malayi (31)(32)(33). However, information about the anatomy and physiology of the protein secretory pathways in filarial nematodes has not been intensively investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The proteins released in vitro by Bma-mf differ from those released by adults and are associated with modulation and evasion of the host immune system, among other potential functions (32,33). As it is accepted that parasite protein secretion plays a fundamental role in host immunomodulation (18), it is reasonable to infer that inhibition of protein secretion would result in the inability of the parasite to neutralize preexisting and induced host effectors at the local and systemic levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data suggest that understanding fully the nature of the excretory/secretory proteins [49][50][51] of the parasite may provide additional insights into those parasiteand Wolbachia -derived molecules that mediate the lymphatic dysfunction seen in LF.…”
Section: Discussionmentioning
confidence: 93%